Breeding Perspective for Silk Quality in Tropical Tasar Silkworm, Antheraea mylitta Drury - Gattu, Renuka; Manda, Sreenivas; Gangupantula, Shamitha (Asian Journal of Biological and Life Sciences, 2017)
Antheraea mylitta, a wild sericigenous insect is a species widely distributed in the form of various ecoraces which are contributing to the livelihood of forest based aboriginals. In the present investigation, certain tasar populations of A.mylitta were studied based on their environmental conditions, phenotypic variability and behavior pattern. The study revealed that some ecoraces are available in many parts of tasar producing states as robust cocoons, while others are found in limited numbers in exclusive areas of natural environs, bestowing their respective unique features. The present study is on breeding of tasar ecoraces is aimed at the improvement of to be bestowed with superior characters i.e., survivability and fecundity of Daba TV and also as one of the probable strategies for enhancing the productivity and quality of tasar raw silk by breeding method.
Keywords: Antheraea mylitta; Breeding; Ecoraces; Phenotypic Variability